2020
DOI: 10.1155/2020/6519236
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional Evolution of Intelligent Cars Human-Machine Interface considering Take-Over Performance and Drivers’ Perception on Urban Roads

Abstract: The study analyzed the drivers’ take-over behaviors in intelligent cars when driving on urban roads and tried to find reasonable dimensions of the human-machine interface. Firstly, the main driving assistance functions in the process of take-over were analyzed based on the entropy theory, and the weight values of each function for the consumer’s purchase intention were calculated. Secondly, we explored the perceived comfortable dimensions of the interactive components under typical interaction modes. By means … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The study was oriented to typical dashboard layouts and used a simple driving simulator to conduct experiments ( Figure 1 ). The simulator was commonly used in driving schools in China, and existing research showed that it could effectively collect people's driving behaviors ( 13 ). Interaction efficiency, eye movement characteristics, mental stress changes and system usability were collected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was oriented to typical dashboard layouts and used a simple driving simulator to conduct experiments ( Figure 1 ). The simulator was commonly used in driving schools in China, and existing research showed that it could effectively collect people's driving behaviors ( 13 ). Interaction efficiency, eye movement characteristics, mental stress changes and system usability were collected.…”
Section: Methodsmentioning
confidence: 99%
“…For example, from the perspective of take-over performance in intelligent vehicles, the average reacting time of older drivers was at least 1.2 s longer than that of young drivers ( 12 ). The in-vehicle HMI dimensions had a significant impact on drivers' task completion time ( 13 ), but a reasonable layout of the dashboard also played an important role in the driver's recognition efficiency. However, at present, people tended to just study the shape and character encoding of instrument panels ( 14 ).…”
Section: Literature Reviewmentioning
confidence: 99%